FAKTOR PENYEBAB KEJADIAN DBD - Ivonne A.V. Gasper; Andi Hardianti; Raden Bagus Edy Santoso; Dahmar Dahmar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Dengue fever, or Dengue Hemorrhagic Fever (DHF), is a public health issue that remains a major challenge to this day, particularly in tropical and subtropical countries. Based on the results of a preliminary survey conducted in the service area of the Kalidoni Community Health Center, it was found that DHF cases remain a fairly common health problem in the community. The general objective of this study is to identify the factors contributing to DBD cases. The study design employed in this research is cross-sectional. The study was conducted in the service area of the Kalidoni Community Health Center. The research was carried out in April 2025. The study population consisted of all household heads residing in the service area of the Kalidoni Community Health Center. The sample size was 60 households. The sampling technique used was Simple Random Sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results indicated an association between knowledge (p-value: 0.038) and the habit of hanging clothes (p-value: 0.042) with the occurrence of DF. It is recommended that the community actively seek information about DF and routinely practice the 3M Plus behavior. Keywords: Toddlers, Mothers' Employment, Mothers' Education